Long-term management of type 2 diabetes with glucagon-like peptide-1 receptor agonists - Courtney H; Nayar R; Rajeswaran C; Jandhyala R (Diabetes, Metabolic Syndrome and Obesity, 2017)
Hamish Courtney,1 Rahul Nayar,2 Chinnadorai Rajeswaran,3 Ravi Jandhyala 4 1Diabetes Department, Royal Victoria Hospital, Belfast, 2City Hospitals Sunderland NHS Foundation Trust, Sunderland, 3Department of Diabetes & Endocrinology, Mid Yorkshire NHS Trust, Dewsbury, 4Medical Affairs, Diabetes, AstraZeneca, Luton, UK Abstract: Continuously reducing excess blood glucose is a primary goal for the management of type 2 diabetes (T2D). Most patients with T2D require glucose-lowering medications to achieve and maintain adequate glycemic control; however, treatment failure may occur, limiting treatment options. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are an emerging therapeutic class that can be prescribed for patients instead of basal insulin after the failure of oral therapies. Recent studies have focused on the durability and tolerability of long-term GLP-1RA therapy. This review summarizes the key efficacy and safety findings from prospective phase 3 clinical studies of at least 76 weeks’ duration for the GLP-1RAs currently approved in the United States and the European Union (albiglutide, dulaglutide, exenatide twice daily [BID], exenatide once weekly [QW], liraglutide, and lixisenatide). Currently, most of the long-term data are from uncontrolled extension studies, and continuous patient benefit has been observed for up to 3 years with multiple GLP-1RAs. Four-year comparative data demonstrated a longer time to treatment failure for exenatide BID than for sulfonylurea, and 3-year comparative extension data demonstrated greater glycated hemoglobin (HbA1c) reductions and weight loss with exenatide QW than with insulin glargine. Currently, the longest extension study for a GLP-1RA is the DURATION-1 study of exenatide QW, with >7 years of clinical data available. Data from DURATION-1 demonstrated that continuous HbA1c reductions and weight loss were observed for the patients continuing on the treatment, with no unexpected adverse events. Taken together, these data support GLP-1RAs as a long-term noninsulin treatment option after the failure of oral therapies. Keywords: albiglutide, dulaglutide, exenatide, liraglutide, lixisenatide, long-term